Marxist archeology in Peru: Genesis, deployment and future - Tantaleán, Henry (2006)
This paper describes the historical development of a theoretical trend in Peru that we will cal! Marxist Archaeology. This archaeology is based in the classical writings ofMarx and Engels, althought like we will see many of the authors made different readings of these authors, not necesarilly rooted on the onthology and epysthemology of Dialectical Mmaterialism. In order to get our aim, we loca te this kind of archaeology inside of its production context as a means to understand in a better way its sociological and ideological perspectives. We will perceive throught our historygraphical analysis that every time that we try to describe any of the studied moments of this marxist archaeology, we willfind one author monopolizing the archaeological scene. We believe that in the case of the first and third moments, this situation was possible because the authors mentioned were organically attached to the peruvian governments. In the second moment, the inexistence of an official political platform concordant or tolerant with the marxism, supossed that an author unrrelated with the official (dominant) academic circles will protagonize, althought in a marginal way, this trend, becoming a necessary figure far the continuity of this way of doing archaeology in the Peru of the twentieth century.